2015
DOI: 10.5120/19563-1321
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Short Text in Social Media: Twitter as Case Study

Abstract: With the huge growth of social media, especially with 500 million Twitter messages being posted per day, analyzing these messages has caught intense interest of researchers. Topics of interest include micro-blog summarization, breaking news detection, opinion mining and discovering trending topics. In information extraction, researchers face challenges in applying data mining techniques due to the short length of tweets as opposed to normal text with longer length documents. Short messages lead to less accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…In our preliminary analysis of a sample of tweets, we observed that the tweets dataset contains both advertisements and nonadvertisements content. As advertisements are irrelevant to our project's objective, we filter them first before analyzing the content using the classification approach [4].…”
Section: B Analytics Tasksmentioning
confidence: 99%
“…In our preliminary analysis of a sample of tweets, we observed that the tweets dataset contains both advertisements and nonadvertisements content. As advertisements are irrelevant to our project's objective, we filter them first before analyzing the content using the classification approach [4].…”
Section: B Analytics Tasksmentioning
confidence: 99%
“…There are several methods that could be implemented in reducing that by selecting the appropriate method. One of them would be a support vector machine or known as SVM (Support Vector Machine) [15]. In terms of NLP, SVM is one of the machine learning models that is often used.…”
Section: Related Workmentioning
confidence: 99%
“…Short-text classification is a common problem in information retrieval (Ji et al, 2014) and has applications in several domains including e-commerce (Yu et al, 2012;Shen et al, 2009), social media (Kateb and Kalita, 2015), healthcare (Pestian et al, 2007) and cognitive-biometric recognition (Pokhriyal et al, 2016). In this paper, we develop a short text classification technique for solving two problems relevant to product search on e-commerce platform: 1) Product Query Classification (PQC) -When the customer enters a free form query, it is important to understand their product type intent to recommend and advertise the relevant products.…”
Section: Introductionmentioning
confidence: 99%